DOKTRIN TANGGUNG JAWAB ATASAN DALAM STATUTA ROMA TENTANG MAHKAMAH PIDANA INTERNASIONAL - , WIBOWO MALIK; , Prof. Dr. Edward O.S Hiariej, S.H., M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The discourse of doctrine of superior responsibility concerns in Indonesia since the Ad-Hoc Human Rights Court for Timor-Leste. Historically, superior responsibility aimed to liable military commander for violations of humanitarian law committed by his or her subordinates. The doctrine was applied for the first time by the International Military Tribunal for the Far East. In the further development, the doctrine was adopted with modifications in the ICTY Statute, the ICTR Statute and the Rome Statute of the ICC. This thesis took questions of interpretation of the doctrine of superior responsibility in the Rome Statute and its implication for the implementation of Indonesian Human Rights Court Act. This thesis research aimed to describe the interpretation of superior responsibility based on the practices and doctrines of international criminal law, particularly Art. 28 of the Rome Statute, in order to synchronize the perception of the application of the doctrine of superior responsibility between the Rome Statute and Indonesian Human Rights Court Act. This research is a normative legal research. The legal materials are the primary legal materials, namely the rules of law related to the doctrine of superior responsibility in the gross violations of human rights, and the secondary legal materials, i.e. the materials which consist of legal literature written by the legal experts, law journals, etc, by literature study. Overall legal materials obtained will be analyzed qualitatively. This research resulted the application parameters of the doctrine of superior responsibility in the context of international criminal law enforcement for the gross violations of human rights.